Focused surface acoustic wave locally removes cells from culture surface. Issue 7 (18th March 2021) - Inui, Takumi; Mei, Jiyang; Imashiro, Chikahiro; Kurashina, Yuta; Friend, James; Takemura, Kenjiro
Abstract : After exposing a plated C2C12 cells culture to PBS, ultrasound from the SAW device transmitted into the cell culture via a coupling water droplet. We can remove cells from an area 6 × 10 −3 mm 2, equivalent to about 12 cells. Abstract : Regenerative medicine and drug development require large numbers of high-quality cells, usually delivered from in vitro culturing. During culturing, the appearance of unwanted cells and an inability to remove them without damaging or losing most if not all the surrounding cells in the culture reduce the overall quality of the cultured cells. This is a key problem in cell culturing, as is the inability to sample cells from a culture as desired to verify the quality of the culture. Here, we report a method to locally remove cells from an adherent cell culture using a 100.4 MHz focused surface acoustic wave (SAW) device. After exposing a plated C2C12 mouse myoblast cell culture to phosphate buffered solution (PBS), ultrasound from the SAW device transmitted into the cell culture via a coupling water droplet serves to detach a small grouping of cells. The cells are removed from an area 6 × 10 −3 mm 2, equivalent to about 12 cells, using a SAW device-Petri dish water gap of 1.5 mm, a PBS immersion time of 300 s, and an input voltage of 75 V to the SAW device. Cells were released as desired 90% of the time, releasing the cells from the target area nine times out of ten runs. In the one trial in ten that fails, the cells partially release and remain attached due to inter-cellular binding. By making it possible to target and remove small groups of cells as desired, the quality of cell culturing may be significantly improved. The small group of cells may be considered a colony of iPS cells. This targeted cell removal method may facilitate sustainable, contamination-free, and automated refinement of cultured cells.